Edukasi Kesehatan dengan Poster untuk Kesiapan Menarche dan Pubertas di SDN 02 Labuhan Sumbawa - Anggraini, Yulida; Lestari, Ana; Rafi’ah, Rafi’ah (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
Adolescence is a critical phase in life, marked by the transition from childhood to adulthood, known as puberty. One of the physiological changes experienced by adolescent girls is Menarche or the first menstruation. Lack of understanding about Menarche can cause anxiety and negative reactions, both psychologically and physically. Health education is essential to equip young girls with the necessary knowledge to face these changes. This community service activity was conducted on January 8, 2025, at SDN 02 Labuhan Sumbawa, aiming to enhance the readiness of 5th and 6th-grade female students in facing Menarche and puberty. The method used was counseling through posters and interactive discussions. Posters were chosen as an educational medium due to their visual nature, making the information more accessible and understandable for children. The results of this activity showed an increase in students' understanding of Menarche and puberty, reducing excessive anxiety among them. Education using posters proved effective in delivering health information and helping young girls prepare for bodily changes with a more positive attitude.